Anti-inflammatory and antinociceptive activities of the ethanolic extract of Pluchea indica (L) less leaf - Abd Hamid @ Abdul Razak, Roslida; A. K., Erazuliana; Ahmad, Zuraini (Società Italo-Latinoamericana di Etnomedicina, 2008)
Ethanolic extract of Pluchea indica leaf (PIL) was used to investigate its anti-inflammatory and antinociceptive activities by using carrageenan - induced oedema model and acetic acid induced writhing test. PIL exhibited significant and dose-dependent anti-inflammatory activity at a dose of 300 mg/kg when administered orally. It is also demonstrated that the i.p administration of PIL at a dose of 10, 30, 100 and 300 mg/kg produced significant inhibition of abdominal constriction induced with 0.6% (v/v) acetic acid in dose dependent manner. These results indicate that PIL exhibits significant anti-inflammatory and antinociceptive effects.